Time of colostrum discharge of more than six hours as a risk factor for physiological jaundice in neonates - Ni Kadek Muliawati; I Gusti Ayu Trisna Windiani; Anak Agung Sagung Sawitri; Luh Seri Ani (Universitas Udayana, 2019)
Background and purpose: Neonatal jaundice is both a physiological and pathological condition. Neonatal physiological jaundice occurs within 3-5 days after the baby is born. Publications about time of colostrum discharge and neonatal jaundice are still limited. This study aims to determine the risk time of colostrum discharge more than 6 hours to physiological jaundice in neonates. Methods: A case control study was conducted at the Sanglah General Hospital in Denpasar from August to December 2017. The number of cases was 55 neonates with physiological jaundice and the number of controls was 55 neonates without physiological jaundice. Cases and controls were selected by consecutive sampling. The occurrence of physiological jaundice was obtained by direct observation and the degree of jaundice was determined based on the division of Kramer's body zone. Neonates with the Kramer grades I and II at the age of 3-5 days were classified as experiencing physiological jaundice (as cases) and neonates with a Kramer grade of 0 at the age of 3-5 days were classified as not jaundice (as controls). Cases were matched with controls by sex and age of the neonates. Data on maternal socio-demographic characteristics, time of colostrum discharge, early breastfeeding initiation and 24-hour breastfeeding frequency were obtained by interview; data on jaundice was obtained by observation while mode of delivery, parity, history of pre-eclampsia, prematurity, neonatal birth weight, history of birth trauma (cephalic hematoma), history of asphyxia and major congenital abnormalities were obtained from medical records. Multivariate analysis with binary logistic regression was carried out to determine the adjusted odds ratio (AOR) time of colostrum discharge . Results: The characteristics of cases and controls were found to be similar in terms of maternal education, neonatal age and sex, parity and pre-eclampsia history. Significant time of colostrum discharge >6 hours was found to be associated with physiological jaundice with AOR=2.57 (95%CI: 1.04-6.37). In this study, variables that were not found to be the risk factors of physiological jaundice in neonates were: cesarean delivery (AOR=0.36; 95%CI: 0.09-1.41; p=0.14), breastfeeding frequency within 24 hours (AOR=2.20; 95%CI: 0.47- 10.23; p=0.31) and early breastfeeding initiation (AOR=0.71; 95%CI: 0.19-2.59; p=0.60) Conclusion: time of colostrum discharge >6 hours is a risk factor for neonatal jaundice. Efforts should be made to accelerate the release of colostrum in order to prevent neonatal jaundice.